Implementation of The Islamic Story Method in Infusing Moral Religion in Early Childhood in TK TAAM Adinda Kepatihan Menganti Gresik - Syaikhon , Muhammad (LPPPM STAI Darul Hikmah Bangkalan, 2020)
. This research is the kind of research the field with the approach descriptive qualitative the title the implementation of the islamic story method in infusing moral religion in early childhood in TK TAAM Adinda Kepatihan Menganti Gresik aimed at described the implementation of the islamic story method in infusing moral religion in TK TAAM Adinda Kepatihan Menganti Gresik as well as the supporting and inhibitors in infusing moral religion in TK TAAM Adinda Kepatihan Menganti Gresik. These research findings can be concluded that the implementation of the islamic story method in infusing moral religion in TK TAAM Adinda Kepatihan Menganti Gresik consisting of preparation, matter, method, media, and evaluation. In terms of preparing, the educator has done various preparation personal and technical well. In the materialistic world, the educator does it started from a model of development education gallop in RPPM (Rencana Pelaksanaan Pembelajaran Mingguan/implementation plan of learning weekly and RPPH (Rencana Pelaksanaan Pembelajaran Harian/implementation plan of learning daily ) as a result of curriculum development 2013 containing about aqidah, syari'ah, dan akhlak. In terms of method, the educator always uses various or ways interesting. In terms of media, educator more often uses media audio and visual than storybooks and slates. In terms of evaluation, an educator does it with the methods question and answer and observation, and dialogue with student guardians. The implementation of a method of islamic story in infusing moral religion in kindergarten TAAM Adinda having factors supporting quality among other educators, the environment and of learning. In addition to having factors barrier between another time, management class, and tools to tell stories. Supporting factors and inhibitors of until current running each other in tandem